Rancang Bangun Sistem Monitoring Keamanan Laboratorium Menggunakan Komunikasi Long Range (LORA) Berbasis Android - Aliffiyah, Muhammad Bayu; Salamah, Irma; Fadhli, Mohammad (Department of Electrical Engineering, University of Patria Artha, 2021)
It is undeniable that wireless communication technology is developing very rapidly, especially in an emergency. For example in the laboratory. The laboratory is a place to carry out practical or research activities that are supported by complete laboratory equipment and infrastructure. Therefore, it is not impossible that the complete laboratory equipment becomes an excuse for people with the aim of committing crimes. The most frequent crime in the laboratory is theft, the thieves usually take advantage of the moment when the laboratory personnel are not in the room and they can take valuables in the room without being noticed by the officers freely. Therefore our goal in this research is to improve security for laboratories with wireless communication technology methods. This technology uses a communication system named Lora equipped with ALOHA protocol based on Android to be able to monitor remotely. The test was carried out at a height of 80 cm and this study resulted in the largest RSSI value of -130 dB at a maximum distance of 600 m with a delay of 29 seconds. Packet loss is affected by distance, so packet loss or data loss will be higher at longer distances.